2018
DOI: 10.1097/md.0000000000011449
|View full text |Cite|
|
Sign up to set email alerts
|

The utility of FDG-PET/CT imaging in the evaluation of multicentric reticulohistiocytosis

Abstract: Introduction:Multicentric reticulohistiocytosis (MRH) is a rare histiocytic disorder that involves the skin, joints, and visceral organs.Case presentation:We report a 67-year-old woman with MRH who presented with a 2-years history of polyarthralgia and skin nodules. Her symptoms were an inflammatory polyarthropathy with punched-out lesions of the distal interphalangeal (DIP) joints of both hands. Doppler ultrasonography of the hands showed large bone erosions with power Doppler signals in the DIP joints. 18F-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
0
8
0
9
Order By: Relevance
“…Of note, in a case report by Asano et al, when Doppler ultrasound revealed large bone erosions, the authors obtained an F‐fluorodeoxyglucose positron emission tomography/computed tomography (FDG‐PET/CT) with results suggesting an inflammatory process; biopsy ultimately helped establish the diagnosis of MRH. Although age‐appropriate malignancy screening with relevant imaging should be part of any MRH work‐up, this report highlighted the utility in joint ultrasonography as a helpful noninvasive imaging modality in diagnosing MRH 7 …”
Section: Case Discussionmentioning
confidence: 91%
“…Of note, in a case report by Asano et al, when Doppler ultrasound revealed large bone erosions, the authors obtained an F‐fluorodeoxyglucose positron emission tomography/computed tomography (FDG‐PET/CT) with results suggesting an inflammatory process; biopsy ultimately helped establish the diagnosis of MRH. Although age‐appropriate malignancy screening with relevant imaging should be part of any MRH work‐up, this report highlighted the utility in joint ultrasonography as a helpful noninvasive imaging modality in diagnosing MRH 7 …”
Section: Case Discussionmentioning
confidence: 91%
“…Due to the background of negative tumour markers in routine serum tests and the lack of symptoms, it can be difficult to detect this type of malignancy by chest HRCT, especially by inexperienced clinicians. In recent years, the application of FDG-PET/CT in MRH has attracted increasing attention (27)(28)(29). FDG-PET/CT is a potentially useful way to detect and evaluate the grade of inflammatory involvement of MRH and to assess the possible associations with malignant neoplasms, as FDG is easily taken up by granulomas and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Otros compromisos detallados son los de la mucosa oral 3,20 , glándulas salivares mayores 4,15 , nódulos submucosos hipofaríngeos 4,21 , nódulos laríngeos 4,22 y nódulos hepáticos 23 . Se han informado casos aislados de RHM con fenómeno de Raynaud y esplenomegalia 4,24 .…”
Section: Manifestaciones Clínicasunclassified